2022
DOI: 10.1136/bmjopen-2021-057400
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of cardiovascular medication in children with congenital heart defects across six European Regions from 2000 to 2014: data from the EUROlinkCAT population-based cohort study

Abstract: ObjectivesAdvances in surgical management strategies have substantially reduced fatality from congenital heart defects (CHD). Decreased infant mortality might be expected, consequentially to result in greater morbidity in older children due to complications later in childhood and adolescence. This study aims to evaluate the use of cardiovascular medication (CVM) as an indicator of disease burden in children born with CHD in the first 10 years of life.DesignPopulation-based cohort study.SettingSix population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As previously described in detail in Damkjaer et al , 12 antiarrhythmic medication is classified according to the Vaughan Williams classification (VWC). 13 Antihypertensive medication and diuretics were classified according to the Anatomical Therapeutic Classification (ATC) system codes reported in the electronic prescription databases.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described in detail in Damkjaer et al , 12 antiarrhythmic medication is classified according to the Vaughan Williams classification (VWC). 13 Antihypertensive medication and diuretics were classified according to the Anatomical Therapeutic Classification (ATC) system codes reported in the electronic prescription databases.…”
Section: Methodsmentioning
confidence: 99%
“…Population‐based studies have shown that children with congenital anomalies are more frequently hospitalised and that, on average, they spend more time in hospital than children without congenital anomalies 6 . Similarly, these children were prescribed more cardiovascular medication 7 and were 80 times more likely to receive a gastrostomy feeding tube than children without congenital anomalies 8 . A higher risk of cancer has been consistently found in children with congenital anomalies, and especially in children with chromosomal anomalies 9–12 .…”
Section: Introductionmentioning
confidence: 99%